2013
DOI: 10.1007/s00540-013-1738-x
|View full text |Cite
|
Sign up to set email alerts
|

High-dose remifentanil suppresses stress response associated with pneumoperitoneum during laparoscopic colectomy

Abstract: Notwithstanding similar hemodynamic responses in all groups, only high-dose remifentanil suppressed both sympathetic responses and the hypothalamus-pituitary-adrenal axis. This result indicates that of these three anesthesia regimens, high-dose remifentanil seems most suited for laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…When the body suffered sudden intense stimulation, both ACTH and COR levels were significantly increased because of stress reaction. Watanabe et al [30] also demonstrated that plasma concentrations of ACTH and COR were both increased during capnoperitoneum. We speculate that the reasons may be: (1) increased intra-abdominal pressure resulted in reduced renal perfusion and then activated the vascular control center of the medulla oblongata, which enhanced sympathetic activation; (2) pain caused by surgical trauma activated the hypothalamus-adenohypophysis-adrenocortical system, which induced elevated ACTH and COR.…”
Section: Discussionmentioning
confidence: 99%
“…When the body suffered sudden intense stimulation, both ACTH and COR levels were significantly increased because of stress reaction. Watanabe et al [30] also demonstrated that plasma concentrations of ACTH and COR were both increased during capnoperitoneum. We speculate that the reasons may be: (1) increased intra-abdominal pressure resulted in reduced renal perfusion and then activated the vascular control center of the medulla oblongata, which enhanced sympathetic activation; (2) pain caused by surgical trauma activated the hypothalamus-adenohypophysis-adrenocortical system, which induced elevated ACTH and COR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that anaesthetic drugs, more specifically the hypnotic etomidate, can suppress adrenocortical synthesis of cortisol . However, many other drugs may have HPA suppressive properties as suggested by small interventional studies in surgical and ICU patients, by observational studies of surgical patients and by animal experiments. Based on the available evidence, we hypothesized that the pharmacological effects of drugs used during surgery or the acute phase of critical illness prior to ICU admission may explain the acute ‘ACTH‐cortisol dissociation’, as observed upon admission to the ICU.…”
Section: Introductionmentioning
confidence: 97%
“…A second limitation is that one cannot exclude additional suppression at the hypothalamic level from analgo-sedative drugs that are used throughout ICU stay, of which opioids are the main component [37]. Indeed, intra-operative opioids and prolonged opioid use for chronic pain have shown to lower plasma ACTH concentrations [3842]. Furthermore, in healthy subjects, morphine blunts the ACTH response to CRH injection at a supra-pituitary level [43].…”
Section: Discussionmentioning
confidence: 99%